Increasing the Efficiency of Growing Garden Products Based on Innovative Technologies (Eurasian Journal of Research, Development and Innovation, 2023)
This article highlights the benefits of using innovative technologies in the cultivation of fruits and vegetables. The author also gives recommendations on the organization of intensive gardens in the conditions of our country